Anxiety and kicking order affect on penalty kicking accuracy / Raja Fitri Shahar Shah Raja Abu Bakar Shah - Raja Abu Bakar Shah, Raja Fitri Shahar Shah (Faculty of Sport Sciences and Recreation, 2020)
Objective: To study the effects of anxiety and kicking order towards the penalty kicking accuracy. Method: 50 amateur players from 10 amateur football clubs in Kuantan were selected for this study. (5 players from each club). Subjects were within the age range of 18 to 31 years old. Data was collected in a Penalty League in Kuantan held by Kuantan Football Association. Permission and consent were granted by the team managers and organizers. After receiving consent, subjects were given Sports Competition Anxiety Test questionnaire to answers within an hour before the competition begins. Afterwards, a coin toss was done to decide the kicking order of teams in the penalty shootout. Lastly, during the penalty shootout, conversion and miss of the penalty kicks were recorded as data. For the data analysis, this study used one way Anova to compare the penalty kicking accuracy of three anxiety levels and unpair t-test to compare the penalty kicking accuracy of first and second kicker. Result: The study showed a significant difference on penalty kicking accuracy between different level of anxiety with a value of .01 and no significant difference of penalty kicking accuracy between the first and second kicker with a value of .49. Conclusion: There is a significant effect of anxiety on penalty kicking accuracy meanwhile there is no significant effect of kicking order on penalty kicking accuracy